2022
DOI: 10.3390/molecules27206989
|View full text |Cite
|
Sign up to set email alerts
|

Lanostane Triterpenoids and Ergostane Steroids from Ganoderma luteomarginatum and Their Cytotoxicity

Abstract: Macrofungus Ganoderma luteomarginatum is one of the main species of Ganoderma fungi distributed in Hainan province of China, the fruiting bodies of which have been widely used in folk as a healthy food to prevent tumors. To explore the potential cytotoxic constituents from G. luteomarginatum, the phytochemical investigation on the ethyl acetate soluble fraction of 95% ethanolic extract from the fruiting bodies of this fungus led to the isolation of twenty-six lanostane triterpenoids (1–26), including three und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The structures of these compounds were established based on their NMR, HRESIMS, IR, ECD, and single‐crystal X‐ray diffraction data. Two known compounds were confirmed to be (3 β ,5 α ,6 α ,22 E )‐5,6‐epoxy‐3‐hydroxyergosta‐8,22‐dien‐7‐one ( 3 ), [ 32 ] and calvasterol B ( 4 ) [ 33 ] by comparing their NMR spectroscopic data as well as specific rotations with those reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…The structures of these compounds were established based on their NMR, HRESIMS, IR, ECD, and single‐crystal X‐ray diffraction data. Two known compounds were confirmed to be (3 β ,5 α ,6 α ,22 E )‐5,6‐epoxy‐3‐hydroxyergosta‐8,22‐dien‐7‐one ( 3 ), [ 32 ] and calvasterol B ( 4 ) [ 33 ] by comparing their NMR spectroscopic data as well as specific rotations with those reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Lanostane-type triterpenes have been examined for their cytotoxicity against different cancer cell lines, including lung, colon, pancreas, and breast cancers. These compounds, including the characteristic ganoderic acids, downregulated the proliferation and growth cycle of the tumor cells [ 53 ]. Even in silico studies have demonstrated their antiproliferative effects through the interaction with nuclear receptors such as the vitamin D receptor, diminishing the cell growth and activating cell differentiation [ 54 ].…”
Section: Discussionmentioning
confidence: 99%